Practical evaluation for two different holonomic wheeled mobile robots - Shenawy, Ahmed el-; Wellenreuther, Andrea; Badreddin, Essameddin (IEEE International Conference on Systems, Man and Cybernetics, 2008, 2008)
This work is a practical evaluation between two different holonomic wheeled mobile robot platforms. The evaluation criteria had been theoretically explained and used on the simulation level in previous publication. The main objective of this paper is evaluating each wheeled mobile robot practically using the proposed criteria. The first robot is the C3P, which has three caster wheels with wheel angular velocities actuation. The second robot is omni-directional wheeled platform with three omni-directional wheels. The inverse and forward kinematics required in the control structure is presented for the practical experiments, which illustrate the performance of each robot. The comparison is done with respect to three main aspects; 1) the mobility, 2) the total energy consumed by each robot in a finite interval of time, and 3) the hardware complexity. A cost functional is obtained to demonstrate the comparison, and a criteria is developed to measure the hardware complexity of each robot. The weight sum method enables the cost functional to show the importance of each aspect and to distinguish between the lowest cost platform with respect to each aspect importance.
Gesehen am 17.06.2019